(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2022)
The chronic progressive course of RA poses the task of doctors to diagnose it as early as possible. However, recognition of RA at an early stage presents significant difficulties. To date, no strictly RA-specific laboratory test has been found. Only a combination of many clinical and laboratory signs can help in the diagnosis of this disease. Therefore, the search for methods to differentiate rheumatoid arthritis among a variety of inflammatory and degenerative diseases of the musculoskeletal system continues. According to modern concepts, connective tissue damage in RA is a consequence of developing immunopathological disorders. The autoimmune nature of RA is evidenced by the detection of rheumatoid factor (RF), circulating immune complexes (CIC), lymphocytes sensitized to connective tissue components, as well as a wide range of autoantibodies (AT). However, it should be noted that the pathological effect of such antibodies is not fully determined. The development and course of RA are associated with changes in the general and immunological reactivity of the body, complex enzymatic and metabolic shifts, in the regulation of which the endocrine system is of great importance. Hormones play an important role in metabolic processes, immunogenesis, cell membrane permeability, ion transport, protein synthesis, and enzyme system activity. Violations of the activity of the endocrine glands can lead to those changes in metabolism in the body that, even without receiving an explicit reflection in the clinical picture, can have an undoubted significance in the features of the clinical course of RA and determine the effectiveness of treatment.